A construção da identidade profissional do professor de Música para a escola de Educação Básica - Joly, Maria Carolina Leme (Universidade Federal de São Carlos, 2017)
This work is the product of a PhD research in Education and focuses on the professional identity of the school’s music teacher. The objectives were: (1) to analyze the identity construction process of the Music teacher, in order to understand the relationships that it establishes with the context of Music Education in Brazilian basic education; (2) understand which are the processes of socialization that influence the construction of the identity of the teacher of Music of basic education; (3) To analyze how different experiences, social relations and contexts influence the identity of Music teachers in basic education. The research question that guided the work was: How is the identity of the music teacher who works in basic school constructed?The key concepts of the research are: Identity, based on the Dubar, Socialization, having Dubar, Berger and Luckman as reference and Culture, based on the productions from Raymond Williams. The methodology is mixed, being bibliographical research, analyzing scientific articles on the subject, and field research, with semi-structured interviews. As data, I analyzed 16 articles from five different countries and interviewed two music teachers, who were admitted to work in the public education system. I concluded with this work that being a musician and being a teacher are two aspects that add up to the professional identity of the Music teacher; that the context, both specific to the classroom and broader: of the city or country in which professionals work, has a strong influence on the formation, consolidation or crisis of the Music teatcher’s identity; and, the recognition and value given by society will open or close the possibilities and potential of musical work in the basic school. The aim of this work is to understand the music teacher’s professional identity in order to contribute with his recognition, his training process and his space of action
The school Music teacher's professional identity construction
Keywords: Educação musical; Professor de música; Identidade Profissional; Socialização; Cultura; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM